2015
DOI: 10.17221/218/2014-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Dihaploid induction in tetraploid durum wheat (Triticum durum L.) using pollen of Imperata cylindrica

Abstract: Chaudhary H.K., Mahato A., Kaila V., Rather S.A., Tayeng T. (2015): Dihaploid induction in tetraploid durum wheat (Triticum durum L.) using pollen of Imperata cylindrica. Czech J. Genet. Plant Breed., 51: 142-147. Doubled haploidy breeding protocols have revolutionized the varietal development programmes in bread wheat, however, the protocols have not proved much efficient in durum wheat. Presently, the durum wheat × maize system is being widely followed for haploid induction but the frequency of haploid devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Earlier, 2,4-D in combination with different growth promoters like, dicamba (Ballesteros et al 2003;Garcia-llamas et al 2004), picloram (Puja et al 2011) and AgNO 3 (Almouslem et al 1998;Inagaki and Hash 1998;Sourour et al 2011) had been tested for efficient haploid induction in durum wheat × maize crosses. Likewise, Chaudhary et al (2015) and, Mahato and Chaudhary (2015) reported the significant role of 2,4-D in haploid production via I. cylindrica-mediated chromosome elimination approach. It is evident from the findings of present study that higher concentrations of 2,4-D (more than 200 ppm) alone is well efficient in producing greater number of haploid embryos.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Earlier, 2,4-D in combination with different growth promoters like, dicamba (Ballesteros et al 2003;Garcia-llamas et al 2004), picloram (Puja et al 2011) and AgNO 3 (Almouslem et al 1998;Inagaki and Hash 1998;Sourour et al 2011) had been tested for efficient haploid induction in durum wheat × maize crosses. Likewise, Chaudhary et al (2015) and, Mahato and Chaudhary (2015) reported the significant role of 2,4-D in haploid production via I. cylindrica-mediated chromosome elimination approach. It is evident from the findings of present study that higher concentrations of 2,4-D (more than 200 ppm) alone is well efficient in producing greater number of haploid embryos.…”
Section: Discussionmentioning
confidence: 95%
“…This technique mainly involves intergeneric hybridization that follows gradual elimination of chromosomes from pollen source during embryonic development producing embryos carrying haploid set of chromosomes from the female genotype (Barclay 1975; Laurie and Bennett 1988;Chaudhary et al 2005). In durum wheat, wide hybridization to create doubled haploids has been carried out with different genera viz., barley (Hordeum bulbossum) (O'Donoughue and Bennett 1994a;Chlyah et al 1999), pearl millet (Pennisetum glaucum) (Inagaki and Hash 1998), maize (Zea mays) (O'Donoughue and Bennett 1994b;Almouslem et al 1998) and Imperata cylindrica (Chaudhary et al 2013;Chaudhary et al 2015;Mahato and Chaudhary 2015) for producing haploid embryos. But, all these pollen sources may not be equally efficient in inducing haploid formation in durum wheat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gynogenesis process: unpollinated ovaries induced after 1 week of culture (a), callus with green shoot after 10 weeks of culture (b), regenerated green plantlets (c) https://doi.org/10.17221/188/2017-CJGPB viability affects the conversion of embryos into plantlets. In addition, the ability to form haploid embryos might depend on the application of silver nitrate and hormone treatment, alone or in combination (Ayed et al 2011a;Chaudhary et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Interspecific or intergeneric crosses has emerged as an efficient method for producing haploid wheat plants (Garcia-Liamas et al 2004;Ushiyama et al 2007;Ayed et al 2011b). Several crosses, wheat × Hordeum bulbosum (Barclay 1975), wheat × maize (Laurie & Bennett 1988), wheat × sorghum (Inagaki & Mujeeb-Kazi 1995) and wheat × Imperata cylindrica (Chaudhary et al 2015) were shown as valid hybridization systems. In recent years, wheat × maize crosses has become a main approach for haploid production in durum wheat (Niu et al 2014).…”
mentioning
confidence: 99%